"C'è una certa angolazione della luce ...": Gli strumenti di previsione qualitativa e di sintesi interpretativa dei fattori ambientali nell'ambito del progetto architettonico e urbano sostenibile - Bovati, Marco (Techne (Florence, Italy : 2011), 2017)
Among the texts that represent an exception, worth mentioning are the volume "The Green Studio Handbook" (Kwok and Grondzik, 2011), which already in the title contains the phrase 'schematic design, as indication of the importance of heuristic studies, and which presents some conceptual diagrams on the intermediate scale (pp. 33, 353 e 359); Hyde's volumes 'Climate Responsive Design' (Hyde, 2000) and 'Bioclimatic Housing: Innovative Designs for Warm Climates' (Hyde, 2008), where we may also find intermediatescale sketches and diagrams (Hyde, 2000, pp. 40-41) and some masterplan examples that include bio-climatic principles (Hyde, 2008, p. 133), in the chapter edited by F. Sartogo and V. Calderaro; and, even more so, Rogora's volume (Rogora, 2012) which devotes an entire chapter, the seventh one, to the description and representation of energy factors of the project site, with some working hypotheses of summary maps of environmental emergencies (pp. 127, 139, 140, 145 and 146), and the important text by Brown and DeKay, 'Sun, Wind & Light, Architectural Design Strategies' (Brown and DeKay, 2001), which sets out diagrams (plans and sections) at the scale of the project site, included in an essay characterised by an approach that already from the introduction explicitly embodies its underlying philosophy4, lending great importance to the schematic design phase and to the integration between a focus on the intermediate scale and the preliminary design phases, investigated through the use of schematic representations, sketches, and freeform drawings of great refinement. [...]the third category divides them into natural and anthropic (man-made), allowing us to investigate their origin with a view to organizing them pursuant to the different level of anthropic or natural dimension that characterizes them and understanding their possible degree of alteration. [...]the integrated character of the proposed maps, consisting in an attempt to intertwine, already at the stage of knowledge of the place, the climatic elements of a quantitative nature and the environmental factors with some outcomes of historical, typological and morphological surveys, in order to highlight their spheres of mutual interaction in the light of an extended notion of context (Los, 2003). [...]there is the attempt of taking this integration hypothesis to its utmost limits, emphasizing the way in which the dialectical relationship between the different components involved (climatic, environmental, historical, typological, morphological) is capable of activating interaction processes between qualitative and quantitative elements, as well as giving rise to dynamics of selection/ interpretation of the factors concerned, for which a key role is played by the designer's culture and sensibility in critically orientating the design consequences of this phase of work.